ANALISIS SPEKTRAL DARI SERAPAN DAN PANTULAN DAUN LAMUN MENGGUNAKAN SPEKTRORADIOMETER TRIOS-RAMSES DI NUSA LEMBONGAN DAN PEMUTERAN, BALI - Alvidita Beatrix Indayani (Indonesian National Institute of Aeronautics and Space (LAPAN), 2020)
Knowledge and technological developments are needed to achieve the 14th sustainable development goals (SDGs), namely life below water.One of the developments in remote sensing technology is hyperspectral data for spectrometry analysis using underwater sensors. This study aims to determine the absorption and reflectance features as well as the specific location of the spectral channels of various seagrass leaf conditions. Spectral measurements were carried out on three species of seagrass, namely Cymodocea rotundata (Cr), Thalassia hemprichii (Th), and Enhalus acoroides (Ea) along with the physical conditions attached to seagrass leaves (green, yellow to brown, black, and covered leaves by epiphytic organisms) in shallow sea waters. Spectral measurements using a spectroradiometer equipped with an irradiance hyperspectral radiometer sensor from TriOS-RAMSES, have a spectral range of 320-950 nm and a spectral channel width of 3.3 nm. The measurement process is done with a Field of View (FOV) angle of seven degrees (70). The continuum removal algorithm is used to identify the spectral response features of various seagrass leaf conditions. The results show the location of absorption channels and reflections close together. The location of the absorption feature occurs in the blue channel region (463-493 nm) and the red-red edge channel (671-674 nm). The location of the reflected peaks in the green channel (560-577 nm) and red channel (648 nm) of various seagrass leaf conditions.